Video-assisted thoracic surgery ( conventional and single-port ) - place and role in the improved management of malignant pleural effusions: review article - D. Valchev; E. Obretenov; D. Petrov (Trakia Journal of Sciences)
MPE management has been changing over the years as this is due both to the technological advancement of mini-invasive surgical methods and to the change in our knowledge about this manifestation of oncology disorder. Advanced cancer disease and poor general condition in most cases do not allow large-volume and duration of surgical procedures. VATS is becoming an increasingly large share of the operating methods of treatment of spontaneous pneumothorax, thoracic trauma, acute pleural empyema, pleural effusion, benign pleural and pulmonary lesions, secondary metastatic and primary malignant lesions - pleural, pulmonary, mediastinal and bilateral location. Diagnostic and therapeutic capabilities of VATS for simultaneous diagnosis and palliative surgical treatment make it the optimal procedure in MPE management. It should be noted that the preliminary assessment of the patient’s condition and local status with an estimate of survival time often undergoes a radical change after the video-assisted surgical procedure. Improvement is reported with an increase of predetermined survival time and improved performance status, which supports the application of more minimally invasive, non-intubated, “awake” single-port VATS.